2019
DOI: 10.1007/s10067-019-04439-y
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity of seasonal and pandemic influenza vaccination in autoimmune inflammatory rheumatic patients—a 6-month follow-up prospective study

Abstract: Introduction Influenza may cause severe complications in patients with autoimmune inflammatory rheumatic disease (AIRD), to whom vaccinations are especially recommended. However, AIRD patients require cautious scrutiny of immunogenicity as they might exhibit poor antibody response to vaccination, especially when taking immunomodulatory medications. Aim The aim was to determine immunogenicity of seasonal and pandemic influenza vaccine in AIRD patients, its timeline/ persistence, and influence of medications on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…156 In patients exposed to rituximab, most studies found a reduced humoral response to pneumococcal, 101,112,115,[126][127][128]135,157 hepatitis B, 136 and influenza vaccination. 73,108,111,116,122,130,142,144 Rituximab exposure did not significantly affect humoral response to seasonal influenza vaccination in patients with autoimmune blistering disease. 104 Blauvelt et al 153 found that patients with moderate to severe atopic dermatitis treated with dupilumab did not have a decreased humoral response to meningococcal and tetanus/diphtheria/pertussis vaccination.…”
Section: Vaccines and Biologicsmentioning
confidence: 88%
“…156 In patients exposed to rituximab, most studies found a reduced humoral response to pneumococcal, 101,112,115,[126][127][128]135,157 hepatitis B, 136 and influenza vaccination. 73,108,111,116,122,130,142,144 Rituximab exposure did not significantly affect humoral response to seasonal influenza vaccination in patients with autoimmune blistering disease. 104 Blauvelt et al 153 found that patients with moderate to severe atopic dermatitis treated with dupilumab did not have a decreased humoral response to meningococcal and tetanus/diphtheria/pertussis vaccination.…”
Section: Vaccines and Biologicsmentioning
confidence: 88%
“…Rituximab [14][15][16][17][18][19][20][21] and MTX 14 22 23 reduce influenza vaccine immunogenicity. Abatacept likely impairs immunogenicity though data are limited.…”
Section: Effect Of Dmard Therapy Of Vaccine Efficacymentioning
confidence: 99%
“…18 Several studies in patients with autoimmune diseases failed to show reduced immune response to influenza vaccination in patients on immunosuppressive therapy with corticosteroids and/ or DMARDs, TNF inhibitors, or IL-6 receptor antagonists compared with either healthy controls or patients not on immunotherapy. [68][69][70] For patients with autoimmune diseases on immunosuppressant therapy, the ability of influenza vaccination to induce an immune response depends on the type of drug therapy used for treatment.…”
Section: Influenza Vaccinesmentioning
confidence: 99%